TAKAFUL MARKET PENETRATION IN MALAYSIA: STRATEGIES TO MOVE FORWARD - Wan Jusoh, Wan Noor Hazlina (Jurnal 'Ulwan, 2023)
The Malaysian Takaful industry has experienced encouraging growth since its inception in 1985. Annual growth rate of the industry has been estimated to be around 20%. Despite such impressive rate of growth, it is believed that the market penetration of Takaful is still low. This is evident from Malaysian Takaful Association (MTA) Annual Report 2021, the market penetration for Takaful was 18.6%. It showed that the level of awareness related to takaful is still relatively low in Malaysia. Therefore, this study aims at exploring the strategies that should be done by relevant authorities to increase takaful market penetration in Malaysia. Library research is used to discuss the strategies that should be taken by relevant authorities to increase the takaful penetration rate in the future. It is found that all relevant parties need to work hand in hand to increase takaful market penetration in Malaysia. The relevant parties here are not limited to Bank Negara Malaysia, MTA, takaful operators and takaful advisors but including higher learning institutions (universities and training institutes) by integrating takaful to academic curriculum.